Effect of particle size on the thermal and mechanical properties of aluminum composites reinforced with SiC and diamond. (15th January 2016) - Tan, Zhanqiu; Chen, Zhizhong; Fan, Genlian; Ji, Gang; Zhang, Jie; Xu, Run; Shan, Aidang; Li, Zhiqiang; Zhang, Di
Abstract: The effect of particle size on thermal conductivity (TC) and bending strength was investigated in the SiC/Al and diamond/Al (Dia/Al) composites for thermal management applications. The results showed that with the particle size of SiC increasing from 7 to 250 μm, the TC of the 40 vol.% SiC/Al composite was improved by 50%, from 182 to 272 W/mK, while the bending strength decreased by 100% from 352 to 175 MPa. Comparatively, with diamond particles increasing from 30 to 200 μm, the TC of the 40 vol.% Dia/Al composite increased by around 52% from 313 to 475 W/mK, and the bending strength declined by 32% from 327 to 223 MPa. Characterization of fracture surface indicated that large SiC particles featured by an irregular shape tended to fracture prior to the Al matrix during loading, while large diamond particles with a regular shape did not have such a tendency. Moreover, diamond particles with a high intrinsic TC contributed to global TC much more than SiC ones with a relatively low TC. Thus, in order to balance thermal and mechanical properties of particulate reinforced aluminum composites, particle size of reinforcements should be well compromised according to their intrinsic properties. Graphical abstract: Highlights: SiC/Al and diamond/Al composites with various particle sizes were fabricated. Effect of particle size on thermal conductivity and bending strength was revealed. Large SiC particles of irregular shapes tend to fracture prior to matrix during loading. Large diamond particles of regular shapes contribute more conduction and strength than SiC. Particle size should be well compromised according to their intrinsic features.